Anatomical and functional correlates of human hippocampal volume asymmetry - Woolard, Austin (2012)
Hemispheric asymmetry of the human hippocampus is well established, but poorly understood. We studied 110 healthy subjects with 3-Tesla MRI to explore the anatomical and functional correlates of the R>L volume asymmetry. We found that the asymmetry is limited to the anterior hippocampus (hemisphere × region interaction: F(1,109) = 42.6, p < .001). Anterior hippocampal volume was correlated strongly with the volumes of all four cortical lobes. In contrast, posterior hippocampal volume was correlated strongly only with occipital lobe volume, moderately with the parietal and temporal lobe volumes and not with the frontal lobe volume. The degree of R>L anterior hippocampal volume asymmetry predicted performance on a measure of basic cognitive abilities. This provides evidence for regional specificity and functional implications of the well-known hemispheric asymmetry of hippocampal volume. We suggest that the developmental profile, genetic mechanisms and functional implications of R>L anterior hippocampal volume asymmetry in the human brain deserve further study.